2014
DOI: 10.2495/eq140281
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production by supercritical water gasification of food waste using nickel and alkali catalysts

Abstract: Supercritical water gasification (SCWG) of food waste was carried out with nickel and alkali catalysts (NaOH, KOH, Ca(OH) 2 , Na 2 CO 3 , NaHCO 3 and K 2 CO 3 ). The food waste was comprised of a variety of food items. The experiment was performed in a batch reactor at supercritical water (SCW) conditions of 400°C and 22.1MPa for 10mins. Hydrogen (H 2 ) gas yield regarding the use of the catalysts was in the sequence; Ni-K 2 CO 3 > Ni-NaOH > Ni-KOH > Ni-NaHCO 3 > Ni > Ca(OH) 2 > Ni-Na 2 CO 3 > No catalyst. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It was proposed that deactivation of La promoted Ni/Al 2 O 3 catalysts is slow as compared to bare Ni/Al 2 O 3 due to anti‐carbon deposition property of La‐Ni/Al 2 O 3 that resulted in better gasification efficiency after the several use. Nickel has also been used in combination of different alkali catalyst such as NaOH, KOH, Ca(OH) 2 , Na 2 CO 3 , NaHCO 3 , and K 2 CO 3 (Amuzu‐Sefordzi et al, 2014) and it was shown that the combination work in the sequence to produce hydrogen; Ni‐K 2 CO 3 > Ni‐NaOH > Ni‐KOH > Ni‐NaHCO 3 > Ni > Ca(OH) 2 > Ni‐Na 2 CO 3 > No catalyst. Results also showed that CO 2 was the main gaseous product.…”
Section: Syngas From Mixed Food Wastementioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that deactivation of La promoted Ni/Al 2 O 3 catalysts is slow as compared to bare Ni/Al 2 O 3 due to anti‐carbon deposition property of La‐Ni/Al 2 O 3 that resulted in better gasification efficiency after the several use. Nickel has also been used in combination of different alkali catalyst such as NaOH, KOH, Ca(OH) 2 , Na 2 CO 3 , NaHCO 3 , and K 2 CO 3 (Amuzu‐Sefordzi et al, 2014) and it was shown that the combination work in the sequence to produce hydrogen; Ni‐K 2 CO 3 > Ni‐NaOH > Ni‐KOH > Ni‐NaHCO 3 > Ni > Ca(OH) 2 > Ni‐Na 2 CO 3 > No catalyst. Results also showed that CO 2 was the main gaseous product.…”
Section: Syngas From Mixed Food Wastementioning
confidence: 99%
“…Results also showed that CO 2 was the main gaseous product. Another study used a few commercial catalysts namely, FeCl 3 , K 2 CO 3 , activated carbon, and KOH (Amuzu-Sefordzi et al, 2014). The results showed that at optimal conditions (500 C temperature, 2 wt% feedstock concentration, and 60 min residence time), the highest hydrogen yield was achieved with KOH catalyst.…”
Section: Supercritical Steam Gasificationmentioning
confidence: 99%
“…In the past years, energy source was obtained only from animal feces, but nowadays, energy can be obtained from all organic wastes with the developing technology. There are studies in the literature on the usability of this organic waste 24–28 . Coffee is widely consumed in the World and thus, there is plenty of coffee waste.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies in the literature on the usability of this organic waste. [24][25][26][27][28] Coffee is widely consumed in the World and thus, there is plenty of coffee waste. The aim of this study is to synthesize a catalyst using defatted spent coffee ground (DSCG).…”
mentioning
confidence: 99%
“…Nickel (Ni) has been reported as it can enhance yield of hydrogen via water gasshifted reaction [7][8][9][10]. Furthermore, there have many of other metals investigated such as platinum (Pt) and ruthenium (Ru).…”
mentioning
confidence: 99%